Pengaruh financial distress, manajemen laba riil and profitabilitas pada tax aggressiveness dengan komite audit sebagai variabel moderasi - Supandi, Serlin; Nikijuluw, Trixie Elvaretta; Astuti, Christina Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Financial Distress, Real Earnings Management and Profitability on Tax Aggressiveness with the Audit Committee as Moderating Variable. The population in this study are manufacturing companies in the Consumer Goods Industry sector in 2017-2021 which are listed on the Indonesia Stock Exchange (IDX). The data used is secondary data with sampling technique using purposive sampling method. Based on this method, of the 50 companies that make up the population, there are 20 companies that meet the sampling criteria for the five-year financial annual reporting period so that in total there are 100 samples. The analytical method used in this research is multiple regression analysis. The results of the analysis show that real earnings management and profitability have a positive effect on tax aggressiveness. Meanwhile, financial distress has no effect on tax aggressiveness. For the audit committee as a moderating variable can weaken the effect of real earnings management and profitability on tax aggressiveness. However, the audit committee cannot weaken the effect of financial distress on tax aggressiveness.